Effect of Variations in Mass Composition of TiO2/Activated Carbon Cassava Peel on Crystal Structure and Size - Fauziyah, Faadhilah; Darvina, Yenni; Ratnawulan, Ratnawulan; Gusnedi, Gusnedi (Journal of Experimental and Applied Physics, 2024)
A battery is a tool used to store electrical energy to obtain electricity so that it can be used to power remotes, cellphones, laptops, cameras and other electronic items. The working indicator of a battery is capacity, its electrochemical cycling capability depends on the anode material. In general, battery anodes are made using graphite. However, graphite has limitations, namely that it can easily cause short circuits. Because graphite has limitations, a replacement for graphite from TiO2 nanocomposites with activated carbon will be made. Nanocomposites are new materials that are formed by combining two or more compounds to produce new properties and have nanoscale dimensions. TiO2 is used because it can reduce short cycles, has good stability, high current density and can increase battery performance capacity. Activated carbon is used to expand the surface of the material to obtain a large capacitance. The activated carbon used in this article is cassava peel from unused waste in order to reduce environmental pollution and increase the economic value of the waste. The aim of this research is to produce TiO2/Activated Carbon nanocomposites to test their crystal structure and size using XRD. TiO2/Activated carbon nanocomposites were obtained using the sol-gel method. Variations in the mass composition of TiO2/Activated Carbon used are 40%:60%, 50%;50%, and 60%:40%. Based on the tests that have been carried out, the smallest crystal size was obtained with a variation of 40%:60%, namely 58.4 nm with a Tetragonal structure for TiO2 while Cubic and Rhombohedral for carbon.